Smart cube : energy harvesting and monitoring sensor - Ang, Yew Swee (2013)
A integration of Microeletromechanical Systems (MEMS) and Complementary Metal-Oxide Semiconductor (CMOS) circuit is designed in cadence. CMOS comprises of the Analog Front End (AFE) and Analog-to-Digital Converter (ADC). AFE comprises of 3 stages which are amplifying stage, inverting stage and rectifying stage. Simulations results for the MEMS, 3 stages of AFE and ADC are shown in this report. The concept on how the respective components work is also explained in this report. Lastly, a Pulse-Width Modulation (PWM) dimming circuit is designed in LT SPICE IV for the integration of the ADC output and Light-Emitting Diode (LED). Simulations results are compared and discussed in this report